Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.
15th International Zeolite Conference, Beijing, PEOPLES R CHINA, AUG 12-17, 2007

Immobilization of penicillin G acylase on amino functionalized mesoporous silica - Sridevi, N.; Pallavi, Shah; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
Penicillin G acylase was immobilized on Amino functionalized mesoporous silica by adsorption method. In this paper we present the effect of penicillin G acylase immobilization on amino-functionalized mesoporous silica and the effect of silica as host matrix on enzyme kinetics. The loading capacity of immobilized Penicillin G acylase is 34 mg protein per 0.5 g of SBA-15. About 65% of the protein was adsorbed on mesoporous silica. The stability of penicillin acylase was enhanced after immobilization on mesoporous silica. The adsorbed enzyme is more stable than the soluble form, both to temperature and pH environments and retained 73% of its activity.
Keywords: Amino functionalized mesoporous silica; Immobilization; Penicillin G acylase; pH and temperature stabilities

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15